The importance of influenza vaccination during the COVID‐19 pandemic. Issue 1 (3rd October 2021) - McCauley, John; Barr, Ian G.; Nolan, Terry; Tsai, Theodore; Rockman, Steven; Taylor, Beverly
Abstract: The COVID‐19 pandemic and the measures taken to mitigate its spread have had a dramatic effect on the circulation patterns of other respiratory viruses, most especially influenza viruses. Since April 2020, the global circulation of influenza has been markedly reduced; however, it is still present in a number of different countries and could pose a renewed threat in the upcoming Northern Hemisphere winter. Influenza vaccination remains the most effective preventive measure that we have at our disposal against influenza infections and should not be ignored for the 2021–2022 season.